2021
DOI: 10.1007/s11042-021-11335-8
|View full text |Cite
|
Sign up to set email alerts
|

Exponential increment of RSA attack range via lattice based cryptanalysis

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
(51 reference statements)
0
1
0
Order By: Relevance
“…These attacks are currently used in much research. According to Boneh and Durfee's heuristic [49], the RSA encryption algorithm is unsafe if exponent d is too small. They demonstrated that, given the public key, an adversary could retrieve the private key when d< N0.292.…”
Section: Rsamentioning
confidence: 99%
“…These attacks are currently used in much research. According to Boneh and Durfee's heuristic [49], the RSA encryption algorithm is unsafe if exponent d is too small. They demonstrated that, given the public key, an adversary could retrieve the private key when d< N0.292.…”
Section: Rsamentioning
confidence: 99%